PERAN KEPALA DESA DALAM MEMOTIVASI PETANI GARAM DI DESA PINGGIR PAPAS KABUPATEN SUMENEP - Kurniawan, Yuda; Widyastuti, Endang (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2024)
In this case, the role of a leader is needed to motivate salt farmers. The aim of this research is to find out the role of the village head in motivating salt farmers in Pinggir Papas village, Sumenep district the role of the village head in motivating salt farmers in Pinggir Papas village, Sumenep district. This research method uses a qualitative descriptive method, namely a type of research with the aim of presenting a complete picture according to the problem being studied. The research results found that the village head's role in motivating salt farmers was effective. Salt farmers say that when they get motivation from the village head, they can maximize their time and energy to produce salt.  The role of the village head in motivating salt farmers is to provide direction, guidance, assistance and discussions related to how to produce quality salt. The conclusion from the results of this research is that the role of the village head in motivating salt farmers in Pinggir Papas village has an impact on the welfare of the people in Pinggir Papas village, the majority of whom are salt farmers. The role of the village head in motivating salt farmers is said to be successful due to the principles possessed by salt farmers, namely, focus on work, efficiency and priorities in work